Humans at work the art and practice of creating the hybrid workplace - Tavis, Anna; Lupushor, Stela (Kogan Page, 2022)
Is your organization strategically prepared for the digital and distributed workplace? Technology, data analytics and artificial intelligence already impact how people work and engage with organizations. A dispersed workforce, greater transparency, social change, generational shift and value chain disruptions are driving new behaviors and expectations from the workplace. Together, these trends are shaping a new era of distributed and digitally enabled network of workers where the work comes to workers instead of the workers going to work. In Humans at Work, employee and workplace experience experts Anna Tavis and Stela Lupushor advocate for the adoption of human-centric practices as a critical and necessary part of adapting work and workplaces to the future of work. Outlining the four factors (digitization of work, distributed workplaces, organizational redesign and changing workforce) driving the dramatic changes in the workplace, each chapter provides examples of how innovative companies are building workplace infrastructure and reshaping norms, serving new markets and adopting new technologies. Filled with examples from both start-ups and established companies, Humans at Work is the workplace leader's guide to building a workplace that creates market value by making work more human"--